Crohn’s disease and dietary recommendations - Beňová, Eva; Boledovičová, Mária; Teplá, Kateřina (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
Crohn’s disease is a chronic non-specific inflammatory bowel disease of any part of the digestive tract, which has a segmental character and digestive tract affects the wall transmurally in all layers. It is a disease of multifactorial etiology. One of the presumed causes of the disease is excessive immune reactions to physiologically occurring intestinal flora in genetically predisposed individuals. Incidence in the Czech Republic is around 4–6 new cases per 100,000 inhabitants per year. Clinical manifestations of the disease are varied and are dependent on localization, extent of disease and the nature of local inflammatory changes. The most common symptoms are diarrhea, abdominal pain and weight loss. The basis for the diagnosis of disease is colonoscopic examination. Treatment of Crohn’s disease is symptomatic and it is a combination of conservative and surgical treatment. Nutritional therapy is a part of the conservative treatment. Nutritional counseling is one of the basic functions of nursing in which nurse holds important educational role in cooperation with the nutritional therapist. Good nutritional status has a positive effect on the overall condition of the patient who better cope with possible acute flare. Dietary recommendations have own specifics in the period of remission and in the period of relapse. Dietary measures are designed to protect the intestinal mucosa irritation. In the remission phase of disease essential dietary measures exist. Diet is no different from a rational diet, and it is very individual. The patient must self-identify foods without the risk of pain or diarrhea. In the relapse phase should be administered diet with low residue – it is necessary to completely eliminate insoluble fiber and hard to digest foods with high fat content. In the phase of relapse may be indicated by the severity of condition parenteral or enteral nutrition.
Keywords: Crohn’s disease; epidemiology; pathogenesis; dietary recommendations